Archetype symbols and altered consciousness: a study of shamanic rituals in the context of Jungian psychology - Sun, Hang; Kim, Eunyoung (Frontiers in Psychology, 2024)
The alteration of consciousness during shamanic rituals is both a physical and mystical phenomenon. It involves psychological and spiritual experiences. Through ritual practices, shamans can connect with archetype within the collective unconscious, utilising trance-inducing techniques for “hallucinatory exploration”. This study surveyed 75 participants to investigate the impact of prototype symbols in Shamanistic rituals on participants' consciousness states focusing on Jungian psychology's concept of archetype . The results indicate that archetype symbols in shamanic rituals can significantly influence participants’ conscious state, leading them to experience a conscious dissolution of the self. Furthermore, archetype symbols have different effects at the stages of consciousness change. In particular, during the “Visionary Restructuralization” stage, archetype symbols, such as patterns, masks, totems and music, brought participants’ consciousness to a peak and caused significant changes to it. These findings suggest that the metaphoric function of archetype symbols plays a crucial role in rituals. Archetype symbols connect the individual to the collective unconscious through visual images and symbolic imagery. They prompt the participants to experience emotional resonances that transcend individual experiences and affect their state of consciousness.